Effect of expectancy and personality on cortical excitability in Parkinson's disease. Issue 9 (29th April 2013) - Lou, Jau‐Shin; Dimitrova, Diana M.; Hammerschlag, Richard; Nutt, John; Hunt, Elizabeth A.; Eaton, Ryan W.; Johnson, Sarah C.; Davis, Melanie D.; Arnold, Grace C.; Andrea, Sarah B.; Oken,; Barry S.
ABSTRACT Our previous studies in Parkinson's disease have shown that both levodopa and expectancy of receiving levodopa reduce cortical excitability. We designed this study to evaluate how degree of expectancy and other individual factors modulate placebo response in Parkinson's patients. Twenty‐six Parkinson's patients were randomized to 1 of 3 groups: 0%, 50%, and 100% expectancy of receiving levodopa. All subjects received placebo regardless of expectancy group. Subjects completed the NEO‐Five Factor Inventory, General Perceived Self‐Efficacy Scale, and Perceived Stress Scale. Cortical excitability was measured by the amplitude of motor‐evoked potential (MEP) evoked by transcranial magnetic stimulation. Objective physical fatigue of extensor carpi radialis before and after placebo levodopa was also measured. Responders were defined as subjects who responded to the placebo levodopa with a decrease in MEP. Degree of expectancy had a significant effect on MEP response (P < .05). Subjects in the 50% and 100% expectancy groups responded with a decrease in MEP, whereas those in the 0% expectancy group responded with an increase in MEP (P < .05). Responders tended to be more open to experience than nonresponders. There were no significant changes in objective physical fatigue between the expectancy groups or between responders and nonresponders. Expectancy is associated with changes in cortical excitability. Further studies are needed to examine the relationship between personality and placebo effect in Parkinson's patients. © 2013 Movement Disorder Society